A fuzzy-based method of assigning train managers to task types - RestelFranciszek J. (Cognitive Sustainability, 2024)
Besides an employee’s skill level, several personal qualities may affect the implementation of a task during job activities. Thus, it might be hypothesised that the effectiveness of railway personnel depends on the relationship between their abilities and the types of available duties. This article presents research results on the compatibility of personnel and performed duties focusing on train managers. This profession is important due to passenger safety, and there is a lower scientific interest in this job than in the case of train drivers. A complex survey has been conducted in cooperation with volunteers from the rail industry. As a result, groups of duties and personnel profiles have also been elaborated in cooperation with railway industry experts. A fuzzy logic-based method was built to classify the train managers. Then, a self-assessment was conducted as the final step; experts were asked to assess the managers’ attitudes. The overall model was tested during validation. The automatised fuzzy-based method recognised 80 % of managers and indicated good clusters.